Czech Republic : Selected Issues. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2018)
This Selected Issues paper examines the state of labor supply in the Czech Republic. The Czech working age population is projected to decline. This has important implications for labor supply and long-term growth. Policies to increase participation rates and retirement age are important and can mitigate the decline in labor force, but are unlikely to offset it. Under a combined moderate policy improvement scenario, the labor force is expected to decline by 3 percent in 2030 and 15 percent in 2050. Under the very optimistic (hence less likely) scenario, the labor force would increase by 3 percentage points by 2030, but then start to decline later with a gap of 8 percent by 2050.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet